2006
DOI: 10.1007/s00104-006-1212-5
|View full text |Cite
|
Sign up to set email alerts
|

Einrichtung eines chirurgischen Trainingslabors an einer Ausbildungsklinik

Abstract: The improvement of surgical skills of trainees in Germany often occurs solely in the operating room. In recent years, several countries have established surgical skills labs as an essential part of surgical education, with the goal of improving and refining surgical skills before clinical application. Several years ago, training units were established by the industry wherein the curricula focused on products of the respective company. Selected training courses are still offered in a few clinics. Presently, lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
0
8
0
6
Order By: Relevance
“…They perform, among other procedures; ten bench-model based vascular anastomoses prior to performing them on patients in the operating room [16,22]. This exemplary attempt to establish a continuous curriculum for surgical residents is one important step towards improving both quality in surgical education and the satisfaction of the trainees in surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They perform, among other procedures; ten bench-model based vascular anastomoses prior to performing them on patients in the operating room [16,22]. This exemplary attempt to establish a continuous curriculum for surgical residents is one important step towards improving both quality in surgical education and the satisfaction of the trainees in surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It is now time to transfer these experiences and build nationwide comprehensive structured surgical curricula to accompany surgical residency programs. This need becomes apparent when considering a survey of general surgery residency programs in the United States that revealed that 86% had specific curricula for teaching book knowledge, but only 45% had curricula for single surgical techniques [16,23]. The most important basic surgical skills needed have been already described and have been compulsory in the graduate training program of the Royal Colleges of Surgery of England, among others, for several years [24].…”
Section: Discussionmentioning
confidence: 99%
“…Befragungen unter Weiterbildungsassistenten in der Chirurgie ergeben, dass fast 2 2 ⁄3 3 der Befragten mit ihrer Weiterbildung unzufrieden sind [10]. Ein Hauptfaktor dabei ist die fehlende Struktur in der Weiterbildung.…”
Section: Establishment Of Multidimensional Structured Training Curricunclassified
“…The effectiveness of simulation-based medical education is indisputable today, especially if it meets best practice requirements in planning and implementation [21], [22], [23]. Today it is virtually considered standard for a faculty to have a skills lab [22].…”
Section: Introductionmentioning
confidence: 99%
“…Today it is virtually considered standard for a faculty to have a skills lab [22]. But the combination of anatomical education - in particular the use of bodies that have been embalmed using the Thiel technique - and simulation-based surgery with teaching of basic surgical skills is innovative and not integrated enough into the degree courses.…”
Section: Introductionmentioning
confidence: 99%